The execution of habitual housing (Acta Judicial Journal, 2019)
The legislative dispersion of the current regulations on mortgage or ordinary foreclosure, which contains specialties for the habitual residence, makes its systematic and unified study advisable and convenient.As we will see, there are so many peculiarities and rights that are recognized to the mortgagor that no one doubts that when the good to be executed is the habitual residence we are faced with a subspecies of the general process of execution, with recognized rights of such importance that it is from all points of convenient view to determine: the specialties of the execution of habitual residence; whether or not the dwelling object of execution has the character of habitual and when or at what time it should be pronounced on it; to whom corresponds the determination of the character of the dwelling; procedure to be followed in case of opposition to such qualification; the very concept of "habitual residence"; at what time the qualification of habitual residence must be referred.There are many uncertainties that are not resolved in the legal regime of execution; and, in addition, those that arise specifically in those executions in which the character of the dwelling does not previously appear, as in the case of ordinary foreclosures and mortgages derived from loans constituted prior to the effectiveness of Ley 1/2013 that introduces this obligation.
Keywords: Habitual housing; Mortgage; Foreclosure